Virulence factor and genetic characterization of Streptococcus pyogenes from clinical isolates - Hamzah, Siti Nur Adila (2019)
Streptococcus pyogenes or group A streptococcus (GAS) is commonly known as a flesh-eating bacterium. Several virulence genes are responsible for this phenomenon and other clinical diseases ranging from mild to life threatening infections. Extracellular toxins such as superantigen streptococcal pyrogenic exotoxins are commonly associated with tissue invasion and initiate the release of cytokinesin S. pyogenes pathogenesis. This study aimed to determine the virulence characteristics of S. pyogenes by haemolysin test and DNase test and the detection of selected toxin genes (speA, speB, speJ, ssa and sdaB) in S. pyogenes isolates. Its genetic relatedness was determined by multilocus sequence typing (MLST). A total of 42 S. pyogenes clinical isolates were collected from Hospital Kuala Lumpur and Hospital Serdang. The isolates were obtained from five different sources which were blood (23.8%), pus (52.4%), tissue (16.7%), wound (4.8%) and throat (2.4%). Regardless of the type of invasiveness, all S. pyogenes produced positive result in haemolysin test. A total of 81.0% of GAS hydrolyzed DNA while only 19.0% negative toward DNase test. Among those with positive DNase, all GAS isolates from throat, tissue and wound contributed positive detection. The highest virulence gene detected was sdaB(83.3%), followed by speB(64.3%), ssa(54.8%), speA(52.4%) and speJ(52.4%). In blood isolates, sdaB gene was highly detected with (80.0%) while in wound isolates, (100.0%) of sdaB, speA, and speB genes were detected as positive findings. All five different virulent genes were detected in all types of samples except speA gene which not been detected in an isolate from throat sample. MLST analysis showed that the most predominant STs were in descending order as follows: ST28, ST473, ST402, ST13 and ST318 (7.14% for each), ST60, ST313, ST205, ST101, ST55 (4.76% for each) and ST300, ST599, ST36, ST25, ST168, ST5, ST426, ST408, ST156, ST31, ST442, ST306, ST147, ST114, ST549, ST89, ST83 (2.38% for each). Based on the phylogenetic tree analysis, eleven pairs of S. pyogenes isolates shared the same branches with the current ancestor such as (HKL14 and HKL23), (HKL1 and HKL22), (HKL17 and HS2), (HKL18 and HS15), (HKL20 and HS18), (HKL2 and HKL6), (HKL5 and HS4), (HS6 and HKL4), (HKL9 and HS5), (HKL10 and HS9) and (HKL19 and HS21).Diverse genetic heterogeneity of GAS isolates in the present study was observed with high distribution of virulence genes. Similarities and differences in ST numbers among GAS isolates shared one common ancestor despite they were isolated from two different locations were also observed. The presence of emm1/(ST28) which is associated with hospital outbreaks worldwide deserves continuous surveillance in Malaysian hospitals.